Exploring the Molecular Level Interactions of Molnupiravir with Serum Albumin- An Analytical Approach - Begum, Shaheen; Rani D, Usha; Somanjeri, Nithya; Taj, S. Naveen (Journal of Neonatal Surgery, 2025)
Molnupiravir is an antiviral agent used to treat mild coronavirus infection. The drug has good oral bioavailability and safety profile. The protein binding profile of molnupiravir with albumin protein is not well characterized. Therefore, to provide deeper insights, the binding characteristics of molnupiravir to bovine albumin serum were explored using spectral techniques and thermodynamic analysis. The Uv-vis spectral analysis revealed moderate affinity between molnupiravir and BSA with a binding constant value of 1.84 x 104 M-1. Molnupiravir quenched the fluorescence spectrum of BSA via a static quenching mechanism. The negative ∆G (-9.53 kJ.mol-1, -11.77 kJ.mol-1, -14.28 kJ.mol-1) for the molnupiravir-BSA complex confirmed spontaneous and exergonic interactions between the molecules.